The essay film as methodology for film theory and practice: Disruptions and expansions for film research - Carolina Sourdis; Gonzalo de Lucas (Alphaville: Journal of Film and Screen Media, 2019)
The essayistic device in film often brings together two temporalities of film creation: the present of the filmed image and the present of the editing process. Through the interaction of both moments, provoked by the critical revision of the raw material and its possibilities of montage, the essay film is constructed through the filmmaker’s exploration of the filmic apparatus, thus revealing film forms as a way of producing and disseminating knowledge. The essay film, therefore, subverts a common theoretical practice: thought is no longer assumed as a procedure for unveiling an image, but it is rather produced by film forms. We claim that the essay film, as a research methodology and a theoretical approximation to film informed by practice, must be unfolded through creative gestures, this is to say, images and sounds that present an audiovisual synthesis of the conscious and intuitive work that both precedes and is synchronic to the moments of filming and editing. This article addresses the essay film through a comparative association of several filmmakers that express and study both concrete and abstract issues of cinema and filmmaking through their own creative practices.